Module Development for Curved Side 3D Geometric Shapes Based on STEAM Approach - Saputra, Edy; Yustinaningrum, Bettri; Nurhayati, Nurhayati (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2023)
Class IX students of SMP Negeri 4 Takengon generally find it difficult to understand the mathematics learning material contained in the school textbook, besides that the teacher also feels that textbooks as teaching materials still do not help students in learning both at school and independently, so it is very necessary to have other teaching materials that can overcome this. Therefore the researcher felt that this research was very suitable to be carried out. This Research and Development (R&D) research uses the Rowntree development model whose goal is to develop math modules with the STEAM approach on curved side space material that is valid and practical for use in junior high school mathematics learning. The development process consists of three stages, namely the planning, development and evaluation stages using the formative evaluation procedure from Tessmer. Based on this development stage, a mathematics module with the STEAM approach has been produced which contains curved side geometrical material and can be categorized as very valid (content validation 4.54 and media validation 4.75) and also very practical based on one to one evaluation (teacher response 96.96% and student response 98.97%) and small group evaluation of 92.11%.